Entrepreneurship and innovation in sport and leisure. - Mosey, Simon (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This innovative textbook explains how sport and leisure organisations can become more entrepreneurial in order to achieve sustainable growth. It introduces key tools, techniques, and approaches that can help sport and leisure organisations put entrepreneurship at the centre of their culture. Drawing on cutting-edge research, innovation discourses, and perspectives from multiple disciplines, the book introduces fundamental concepts in entrepreneurship, innovation, and enterprise, such as digitalisation, research and development (R&D), diversication, extendibility, and sustainability. It highlights future innovation challenges, provides innovative solutions, and introduces a new diagnostic tool for managing entrepreneurship and innovation. The book presents insights on everyday management challenges from experienced industry practitioners and considers the importance of social enterprise and social entrepreneurship at a time of austerity, recession, and increasing uncertainty. Full of real-world cases and scenarios, as well as useful features to encourage critical reection, this book is essential reading for any course on entrepreneurship taken as part of a degree course in sport management leisure, sports studies, recreation, event studies, entertainment management or tourism. It is also fascinating reading for practitioners looking to improve their professional skills.
OCLC-licensed vendor bibliographic record.
Keywords: Sports administration; Entrepreneurship; Sports -- Technological innovations; Leisure -- Economic aspects; BUSINESS & ECONOMICS / Entrepreneurship